2023
DOI: 10.1021/acsbiomaterials.3c00579
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of π–π Stacking Peptide-Contained Double Network Hydrogels

Abstract: Since the physical properties are similar to native extracellular matrices, double network (DN) hydrogels have been studied extensively in the tissue engineering. However, the double chemical crosslinked DN hydrogel is limited by poor fatigue resistance. π–π stacking is a non-covalent bonding interaction, which is essential to maintain and self-assemble the three-dimensional structure of biological proteins and nucleic acids. In this study, a robust polyethylene glycol diacrylate (PEGDA)/FFK hybrid DN hydrogel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Molecules containing aromatic ring structures tend to pile up on each other through π–π-stacking, forming organized fibers or nanostructures that facilitate the formation of self-assembled hydrogels. 22 …”
Section: Delivery Of Chemical Agentsmentioning
confidence: 99%
“…Molecules containing aromatic ring structures tend to pile up on each other through π–π-stacking, forming organized fibers or nanostructures that facilitate the formation of self-assembled hydrogels. 22 …”
Section: Delivery Of Chemical Agentsmentioning
confidence: 99%
“…For instance, diphenylalanine (FF) is a well‐known peptide sequence for its ability to self‐assemble into nanotubes [66] . In one example, a double network hydrogel suitable for drug delivery applications was synthesized by chemically cross‐linking a Phe‐Phe‐Lys peptide to polyethylene glycol diacrylate polymers via Michael addition [67] . Because of the π‐π stacking interactions of FF, a second layer of cross‐linked network resulted in a hybrid double network hydrogel.…”
Section: Peptide and Protein Nanostructure Formationmentioning
confidence: 99%
“…[66] In one example, a double network hydrogel suitable for drug delivery applications was synthesized by chemically cross-linking a Phe-Phe-Lys peptide to polyethylene glycol diacrylate polymers via Michael addition. [67] Because of the π-π stacking interactions of FF, a second layer of crosslinked network resulted in a hybrid double network hydrogel. Preliminary data suggested that the hydrogel maintained favorable characteristics (mechanical properties, slow degradation) even in blood and in vitro cell culture, supporting the potential use in drug delivery and other applications such as tissue engineering.…”
Section: Assemblies Through Hydrophobic Effectmentioning
confidence: 99%
“…π-Stacking (or simply stacking) interactions, i.e. noncovalent attractive interactions between two planar moieties, play an important role in supramolecular organic, 1–4 organometallic 5–8 and bioorganic 9–11 chemistry, molecular recognition, 12,13 and materials science. 14–18 In the vast majority of relevant studies, aromatic compounds are applied as stacking coformers, while hybrid stacking, which occurred between organic and organometallic or organic and inorganic planes, has received very little attention.…”
Section: Introductionmentioning
confidence: 99%